2017
DOI: 10.1021/acs.jced.7b00238
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Benzoin in Six Monosolvents and in Some Binary Solvent Mixtures at Various Temperatures

Abstract: The solubility of benzoin in monosolvents (acetone, ethyl acetate, methanol, ethanol, 1-propanol, and 1-butanol) and binary solvent mixtures (ethyl acetate + methanol, ethyl acetate + ethanol) was measured using UV–vis spectroscopy at temperatures ranging from 283.15 K to 323.15 K. It can be seen from the data that the solubility of benzoin increases expectedly as temperature increases in a given solvent or solvent mixture, the solubility in acetone is maximum among six monosolvents which could be well explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 47 publications
3
38
2
Order By: Relevance
“…In addition, the value of Δ mix S is positive, which follows the principle of entropy increasing, and the dissolution process of aspirin in mixed solvents is entropy-driven. Generally, these results are expected and consistent with general thermodynamics theory …”
Section: Resultssupporting
confidence: 90%
“…In addition, the value of Δ mix S is positive, which follows the principle of entropy increasing, and the dissolution process of aspirin in mixed solvents is entropy-driven. Generally, these results are expected and consistent with general thermodynamics theory …”
Section: Resultssupporting
confidence: 90%
“…In alcohol solvents, except for isopropyl alcohol and 2-butanol, the solid–liquid equilibrium data of 3-amino-2-methylbenzoic acid at the whole temperature range is ranked as methanol > ethanol >1-propanol >1-butanol > isobutyl alcohol. It can be concluded that the solubility of 3-amino-2-methylbenzoic acid is positively related to the polarity of the solvent, following the “like dissolves like” rule. …”
Section: Resultsmentioning
confidence: 99%
“…The λ h equation, which is first proposed by Buchowski et al, is frequently used to describe the relationship between solubility and temperature and is expressed as eq , where λ and h are the model parameters, T is the absolute temperature, and T m is the melting temperature of the solute. The λ value reflects the nonideality of the solution.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%